A Virtual Pedagogical Model Centered on E-Activities - Silva-Quiroz, J (EDIT UM-EDICIONES UNIV MURCIA, 2017)
The use of Learning Management Systems (LMS), have increasingly been incorporated in teaching to supplement class time or introduce e-learning modalities. However a poor use of LMS is noted for innovation in the educational proposals. A relevant and studied use of networked learning methodologies, could contribute to the use of LMS for designing virtual learning environments (EVA) innovative, that give life to pedagogical models privileging virtual online learning by doing, allowing for different learning styles and build on students skills associated with independent learning, networking and collaborative. It requires a methodological change that allows to move from a content-centric and teacher-centered approach to one focused on e-activities and the learner. This article presents a proposal for a pedagogical model focused on online e-activities. A space for the construction of knowledge, within a learning into community, based on the online instructional design, where activities are central, coordinating collaboration, mentoring, resources, content and platform. The model is flexible and adapting in different contexts, themes and types of students.